Complete Genome Sequence of Methylosinus sp. Strain C49, a Methane-Oxidizing Bacterium Harboring phaABC Genes for Polyhydroxyalkanoate Synthesis - Yasuda, Shohei (Microbiol Resour Announc, 2020)
We report a complete genome sequence of Methylosinus sp. strain C49, a methane-oxidizing bacterium (MOB) in the class Alphaproteobacteria, isolated from MOB-enriched biomass. The genome encodes the functional genes for methane oxidation (pmoA) and polyhydroxyalkanoate (PHA) biosynthesis (phaABC). Deciphering the genome will help research toward PHA production by MOB.